ISIS Violations of International Law “Iraq as a model” - الغراوي, فاضل عبد الزهرة (Journal of Legal Sciences, 2021)
The Iraqi people were subjected to the most brutal crime in the history of humanity when ISIS violated the rights system and targeted women, children, civilians, minorities, religion, belief and the right to education and committed many crimes of genocide and crimes against humanity and the abandonment of millions of citizens and the recruitment of thousands of children, which constituted a flagrant violation of human rights and international law It emphasizes the gravity of the threat to international peace and security by the organization and its associated individuals, groups, institutions and entities, including foreign terrorist fighters.          That the legal characterization of ISIS in the context of international law confirms that it does not have a legal personality as a state and has not been recognized by the states and does not have a geography or a specific people until it can be discussed that it is a state in which the pillars of the states defined by international law are available or not, and that the Security Council condemned ISIS organization on Considering that what he is doing constitutes a serious violation of human rights, genocide crimes and crimes against humanity in violation of the provisions of international humanitarian law and human rights law.